Robinson Crusoe - Defoe, Daniel (Hong Kong Oxford university press, 2005)
While the Americas had long been known to Europeans, it still remained a land of mystery and brutality. Robinson Crusoe is an epic story of a prodigal son who finds himself marooned on an uninhabited island off the coast of South America. Death was always around the corner, but survival was the only option
3-5
Keywords: Fiction -- Adventure